ANALYSIS AND DEVELOPMENT OF SOFTWARE AS A SERVICE-BASED PRIVATE CLOUD COMPUTING SYSTEM FOR AT STATE SENIOR HIGH SCHOOL 1 METRO - Tri Nurul Fajarotun; RZ. Abdul Aziz (Prosiding International conference on Information Technology and Business (ICITB), 2020)
This research discussed the analysis and development of the software as a service-based (SAAS) private cloud computing system at State Senior High School 1 Metro. The objective of this study was providing both theoretical and practical benefits especially for State Senior High School 1 Metro so that it presented an integrated data center for the future. The SaaS-based private cloud computing system was discussed only through the prototype model. The objective of this study was developing the SaaS-based private cloud computing system for sharing data or files (e.g., student data, teacher data, academic files, and learning files) at The State Senior High School 1 Metro. The data collecting technique used in this study were through observations and interviews. The result of the data analysis was that The State Senior High School 1 Metro needed a software-based private cloud computing application that was able to be accessed by students, teachers, and academic staff. The result of this study was that the software-based private cloud computing application was able to facilitate State The Senior High School 1 Metro to access the data and files because the data and files needed to be integrated.Keywords: Private Cloud Computing, Software as a Service (SaaS), Prototype